Informality in Latin America and the Caribbean - Loayza, Norman V.; Servén, Luis; Sugawara, Naotaka (Washington, DC: World Bank, 2012)
This paper studies the causes and consequences of informality and applies the analysis to countries in Latin America and the Caribbean. It starts with a discussion on the definition and measures of informality, as well as on the reasons why widespread informality should be of great concern. The paper analyzes informality's main determinants, arguing that informality is not single-caused but results from the combination of poor public services, a burdensome regulatory regime, and weak monitoring and enforcement capacity by the state. This combination is especially explosive when the country suffers from low educational achievement and features demographic pressures and primary production structures. Using cross-country regression analysis, the paper evaluates the empirical relevance of each determinant of informality. It then applies the estimated relationships to most countries in Latin America and the Caribbean in order to assess the country-specific relevance of each proposed mechanism.